2019
DOI: 10.4103/1735-5362.258493
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and cytotoxic evaluation of novel quinozalinone derivatives with substituted benzimidazole in position 3

Abstract: Quinazolinone and benzimidazole are both fused heterocyclic compounds which have shown valuable biological properties including cytotoxic, antibacterial, and antifungal activities. In this study, a series of novel quinazolinone derivatives substituted with benzimidazole were synthesized in two parts. In the first part 2 - phenyl - 1 H - benzimidazol - 6 - amine ( 4 ) was synthesized from the reaction of 4-nitro-o-phenylenediamine and benzoic acid. In the second par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…reported the synthesis and cytotoxic evaluation of quinazolinone- benzimidazole hybrid derivatives against MCF-7 and HeLa cell lines. Cytotoxicity results revealed that compounds with phenyl and nitrophenyl substitutes on C2 of the quinazolinone ring had the lowest cytotoxic activity against both cell lines and compounds with aliphatic substituents in this position had the highest potency (30). Other hybrids of quinazolinone-triazole were recently reported by Jafari et al .…”
Section: Discussionmentioning
confidence: 99%
“…reported the synthesis and cytotoxic evaluation of quinazolinone- benzimidazole hybrid derivatives against MCF-7 and HeLa cell lines. Cytotoxicity results revealed that compounds with phenyl and nitrophenyl substitutes on C2 of the quinazolinone ring had the lowest cytotoxic activity against both cell lines and compounds with aliphatic substituents in this position had the highest potency (30). Other hybrids of quinazolinone-triazole were recently reported by Jafari et al .…”
Section: Discussionmentioning
confidence: 99%
“…[32] Very recently, tetrahydrobenzimidazo [2,1-b]quinazolines have been reported to show antioxidant and anticancer activity. [33] In the past three decades, multicomponent reactions (MCRs) have been widely used for the synthesis of organic compounds. [34] In this procedure, the product is simply formed in a single step from starting materials without separation and purification of intermediates from reaction media.…”
Section: Introductionmentioning
confidence: 99%
“…[ 30 ] Besides, a number of reports exist about fused benzimidazoquinazolines. [ 31–33 ] Benzimidazo[1,2‐c]quinazolines have been used as antimicrobial [ 31 ] and antiviral agents as well as interferon inducers. [ 32 ] Very recently, tetrahydrobenzimidazo[2,1‐ b ]quinazolines have been reported to show antioxidant and anticancer activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cancer is moving to be a significant health problem in the world . According to a World Health Organization (WHO) report, cancer is the second leading cause of death globally and is responsible for an estimated 9.6 million deaths in 2018 .…”
Section: Introductionmentioning
confidence: 99%